Pemanfaatan Difusi Gerak Berbasis AI untuk Transformasi Desain Berbasis Keausan Sederhana Wastra Nusantara - Sunandar, Agus; Kusuma, Ajeng Atma; Ahsan, Rizka Sarah Heydarina Fathima; Rahayu, Sri Eko Puji; Zakaria, Muhammad Hisyam Bin (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Modest wear is a clothing trend with loose, closed, and comfortable cuts. This is not only synonymous with Muslim clothing but has also become an important component of the fashion industry around the world. By combining the Archipelago wastra such as batik, weaving, and songket, modest wear is growing rapidly in Indonesia as a representation of the richness of local culture. However, changing the traditional modest clothing style to the digital age is still difficult, especially with the adoption of modern technologies such as artificial intelligence. The purpose of this study is to use AI-Based Motion Diffusion to transform the design of Nusantara wastra-based modest clothing from 2D images to 3D dynamic animation visualizations. This technology can enrich cultural narratives, make products more attractive, and open up opportunities in the global market. However, collaborative efforts are needed to introduce and apply technology in the creative process because local designers do not understand it. Need analysis, design development, expert validation, and product refinement are all parts of the research conducted using Borg & Gall's research and development (R&D) model. After the data were collected through observation, interviews, and questionnaires, a qualitative descriptive analysis was performed. The results of the research are expected to produce a digital prototype of fashionable clothing based on Nusantara wastra that is innovative, adaptive, and competitive around the world through artificial intelligence-based motion animation. The focus of this research lies in the strategic need for the digital transformation of the Indonesian fashion industry, especially with the aim of introducing the archipelago to the global industry using artificial intelligence technology.